: A novel gene fusion in malignant melanoma - Jiyun Lee; Jeeyun Lee; Sang Duk Hong; Kee-Taek Jang; Su Jin Lee (Precision and Future Medicine, 2018)
Oncogenic gene fusions have been identified in many cancers, and many serve as druggable targets for therapy. Fibroblast growth factor receptor (FGFR) gene aberration is known to be associated with tumor progression and resistance to anticancer therapy. Here we report the first case of malignant melanoma harboring a FGFR3-TACC3 (transforming acidic coiled-coil containing protein 3) fusion, which appears to be a promising potential therapeutic target.